Mogamulizumab in combination improves clinical outcomes in relapsed and refractory Sézary syndrome - Pilkington, Jordan; Ly, Sophia; Kayishunge, Delice; Gentille, Cesar; Wong, Henry K. (Frontiers in Hematology, 2025)
IntroductionSézary syndrome (SS) is an aggressive variant of cutaneous T-cell lymphoma (CTCL) that presents with generalized erythroderma, lymphadenopathy, peripheral blood involvement, and severe pruritus. Unfortunately, the disease can relapse or progress and generally has a poor prognosis. Mogamulizumab is a targeted monoclonal antibody that has been shown to be effective in relapsed disease, with particular benefit in the blood compartment, and has received the U.S. Food and Drug Administration (FDA) approval for CTCL. Data regarding the combination of mogamulizumab with other systemic treatments for CTCL are limited. Here, we present clinical outcomes in a real-world setting where patients with SS were treated using a mogamulizumab-based multi-agent approach.Methods and resultsWe conducted a retrospective chart review of patients in a Cutaneous Lymphoma Clinic and identified 10 patients that met the International Society for Cutaneous Lymphomas (ISCL)/European Organization of Research and Treatment of Cancer (EORTC) diagnostic criteria for SS and were treated with mogamulizumab. These patients received at least four prior therapies, including systemics and topicals. All patients received mogamulizumab in addition to other systemic therapies. Responses were commonly observed in the blood after the first cycle. Global response, determined by assessment in four compartments including the skin, blood, viscera, and lymph nodes, identified four patients that achieved complete remission, three with partial response, two that maintained a stable disease, and one patient that experienced disease progression. The therapies most frequently used in combination were bexarotene and interferon. The median duration of response in our patient population was 23.5 months.ConclusionIn this case series, a multi-agent approach combining mogamulizumab with traditional CTCL systemic agents was well tolerated and was effective in the treatment of relapsed or refractory SS and led to a period of extended clinical improvement.